The Capacities of Syncretism of the Word in Nominative Case in Russian Language and Comparing It with Persian - شفقی, مریم (LANGUAGE ART, 2018)
Syncretism is the syntactic property of a member of the sentence that expresses more than one syntactic meaning all at once. The Syncretic nominative refers to one-member sentences in which the nominative is also the predicate at the same time. Furthermore, some adjectives, comparatives, and participles in Russian and Persian language are widely used as nouns and nominatives. Iranian grammarians discuss the syntactic properties in terms of nominal sentences (semi-sentences). Nominal sentences do not have verbs and, unlike one-member sentences, may comprise more than one member. One-member sentences are usually exclamatory syntactic structures with a special intonation. They are divided into two main groups based on their being voluntary or involuntary. Involuntary one-member sentences are used to warn the addressee about an immediate danger, attract his/her attention, or ask him/her to be careful, such as: Пожар! /pazhar/ (Fire!) or in Persian: ɂātiʃ!. Voluntary one-member sentences are used as a demanding action, such as Тишина! /tišina/ (Silence!) or in Persian: sāket!